A vida administrada do animal laborans no contexto contemporâneo: reflexões a partir de Hannah Arendt - Amaral, Janice (Universidade do Vale do Rio dos Sinos, 2023)
This work aims to investigate the administered life of homo laborans and the possibility of action, using as the research foundation Hannah Arendt's work “The Human Condition” as well as the concepts of labor, action and work, seeking to evaluate how we can think about these concepts in terms of how the dimension of active life could be seen as autonomous and free. We will present the ideas of Lazzarato, philosopher and sociologist, to discuss the administered life in contemporaneity and to compare with Arendt's ideas, concluding that the perspective that action and freedom are only possible in the public sphere is insufficient to understand the complex relationships between the individual, work, and society in contemporaneity.
Keywords: Hannah Arendt; Lazzaratto; Homo laborans; Algoritmos; Vida administrada; Algorithms; Life management; ACCNPQ::Ciências Humanas::Filosofia